Effect of circular hollow section on the strength of foamed concrete beam with processed spent bleaching earth as partial replacement of cement - Tan, Soon Meng (2018)
Beam is a structural member made up of steel, concrete, wood and composite material which span horizontally between supports. Generally, the reinforced concrete beam is the preferred choice as structure element in the construction areas. However, the self-weight of reinforced concrete beam had significantly affected the total dead loads if the structures and applied stresses transferred to the foundation. The weight problem has been overcome by using foamed concrete (FC) because it has lower density than normal concrete. Processed Spent Bleaching Earth (PSBE) is the SBE that has been treated and can be used as a partial replacement for cement in the foamed concrete due to its pozzolanic effect. Objective of this study is to determine the maximum load of flexural beam by using four point bending test (according to the ASTM D6272), the deflection of beam, and the mode of failure of the flexural beam. The density of designed foamed concrete was 1600 kg/m3. 30% of PSBE inserted are the replacement of cement There are four types of beam were prepared include controlled FC beams as solid beam without hollow section (Beam 1), hollow beam with the 20mm diameter circular opening ( Beam 2), hollow beam with the 50mm diameter circular opening ( Beam 3), and hollow beam with the 60mm diameter circular opening ( Beam 4). The dimensions of all beams are same which are (150mm x 200mm x 1500mm) and each beam prepared for 3 units for testing. 4 Linear Variable Displacement Transducer are allocated during the 4 point bending test and the deflection are recorded and analysed. The beams were white painted in order to vision cracking pattern. The cracking pattern are recorded when load applied until the beams failure. The flexural strength of the Beam 1, 2, 3 and 4 was 0.902 N/mm², 0.754 N/mm², 0.664 N/mm², and 0.576 N/mm² respectively. The beams experienced vertical crack also known as ultimate crack because there is no reinforcement in the beams. In order to increase the flexural strength and deflection of beam, the reinforcement should be implemented. The quality control of foam must be monitored in order to get the desired density and concrete strength. Hence, the flexural strength and deflection of circular hollow section decreased as the size of hollow increased. Thus, the deflection of hollow beam decreased with the increase of size of opening. All the beams were undergo vertical cracking as there is no reinforcement.